Structural characterization of CYP260A1 from Sorangium cellulosum to investigate the 1α‐hydroxylation of a mineralocorticoid. Issue 24 (23rd November 2016) - Khatri, Yogan; Carius, Yvonne; Ringle, Michael; Lancaster, C. Roy D.; Bernhardt, Rita
Abstract : In this study, we report the crystal structure of the cytochrome P450 CYP260A1 (PDB5LIV ) from the myxobacterium Sorangium cellulosum So ce56. In addition, we investigated the hydroxylation of 11‐deoxycorticosterone by CYP260A1 by reconstituting the enzyme with the surrogate redox partners adrenodoxin and adrenodoxin reductase. The major product of this steroid conversion was identified as 1α‐hydroxy‐11‐deoxycorticosterone, a novel Δ4 C‐21 steroidal derivative. Furthermore, we docked the substrate into the crystal structure and replaced Ser326, the residue responsible for substrate orientation, with asparagine and observed that the mutant S326N displayed higher activity and selectivity for the formation of 1α‐hydroxy‐11‐deoxycorticosterone compared to the wild‐type CYP260A1. Thus, our findings highlight the usefulness of the obtained crystal structure of CYP260A1 in identifying biotechnologically more efficient reactions. Abstract : Crystal structure of CYP260A1 has been solved. CYP260A1 converts 11‐deoxycorticosterone into novel steroidal derivatives with 1α‐hydroxy‐11‐deoxycorticosterone as a major product. The mutant S326N of CYP260A1 showed higher activity and selectivity for the production of 1α‐hydroxy‐11‐deoxycorticosterone.